DEVIANT AND CONFORMING MOTORIST BEHAVIOR AT A FOUR-WAY STOP - Eisenman, Russell (Acta Scientiae et Intellectus, 2024)
One hundred observations of motorist behavior at a four-way stop revealed frequent deviant behavior, i. e. the motorists often violated the rules/laws for the four-way stop situation. Specific examples of how these violations occurred are provided. Possible explantions are presented, including possible cultural differences in driving in this USA border town near Mexico.